Optical properties of Ti:Al2O3 single crystal - Kusuma, Hamdan Hadi; Saidin, Mohamad Khairi; Ibrahim, Zuhairi (Faculty of Science, 2009)
Optical transmission and absorption spectra of Ti:Al2O3 single crystal have been determined in the region of UV-vis and infrared at room temperature. The main absorption peaks at 491 nm and 562 nm, the weak infrared absorption band at 650 nm and the strong UV absorption band below 300 nm are observed. The absorption coefficient alpha was determined in the visible range while the optical band gap have been determine using the relation of alpha 1/2 vs (hv) plot. The refractive index is discussed in the vicinity of Fresnel's equation. In particular, the Sellmeier equation was determined in the range visible region by means on non-conventional method based on the measurement of refraction by using UV-visible spectroscopy. The refractive indices are forward to decrease from 3.71 to 1.28 in the wavelength range 400 - 800 nm